Immediate functional progression program in adolescent athletes with a spondylolysis. (November 2021) - Selhorst, Mitchell; MacDonald, James; Martin, Lisa C.; Rodenberg, Richard; Krishnamurthy, Ramkumar; Ravindran, Reno; Fischer, Anastasia
Abstract: Objective: To assess the preliminary evidence for the efficacy and safety of an immediate functional progression program to treat adolescent athletes with an active spondylolysis. Design: Prospective single-arm trial. Setting: Hospital-based sports medicine and physical therapy clinic. Participants: Twelve adolescent athletes (14.2 ± 2 years, 25% female) with an active spondylolysis. Main outcome measures: Clinical outcomes included time out of sport, Micheli Functional Scale (Function and Pain) and adverse reactions. Clinical outcomes were assessed at baseline, 1 month, 3 months and 6 months. Magnetic resonance imaging was performed at baseline and 3 months to confirm diagnosis and assess healing of lesion. Results: Eleven participants (92%) fully returned to sport in a median time of 2.5 months (75 days; interquartile range 55 days, 85 days). All participants demonstrated marked improvements in pain and function by the end of the program. One participant (8%) had an adverse reaction during care with a significant recurrence of LBP and had not returned to sport by 6 months. Magnetic resonance imaging demonstrated improvement of the spondylolytic lesion in all but one participant. Conclusion: The immediate functional progression program appears a viable method for treating active spondylolysis and warrants future research. Highlights: The physical therapy program is viable for young athletes with spondylolysis. Young athletes were able to make a full return to sport 2.5 months from diagnosis. 90% of participants demonstrated healing of spondylolytic lesion at three months.